2021
DOI: 10.3390/nu13103434
|View full text |Cite
|
Sign up to set email alerts
|

The “Adipo-Cerebral” Dialogue in Childhood Obesity: Focus on Growth and Puberty. Physiopathological and Nutritional Aspects

Abstract: Overweight and obesity in children and adolescents are overwhelming problems in western countries. Adipocytes, far from being only fat deposits, are capable of endocrine functions, and the endocrine activity of adipose tissue, resumable in adipokines production, seems to be a key modulator of central nervous system function, suggesting the existence of an “adipo-cerebral axis.” This connection exerts a key role in children growth and puberty development, and it is exemplified by the leptin–kisspeptin interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 204 publications
0
7
0
Order By: Relevance
“…In adulthood, hypertriglyceridemia, hyperglycemia, hypertension, and increased waist circumference, which in turn is related to insulin resistance (IR), are some of the criteria used to define the MetS. However, criteria for establishing the diagnosis of MetS in childhood have not yet been clearly defined ( 2 , 3 ), although both fatty liver and increased intima thickness have been described already in overweight children ( 4 , 5 ). The need to shed light on the MetS in childhood has led to the identification of some peptides whose serum levels are closely related to the development of IR ( 2 , 6 – 8 ), including neudesin.…”
Section: Introductionmentioning
confidence: 99%
“…In adulthood, hypertriglyceridemia, hyperglycemia, hypertension, and increased waist circumference, which in turn is related to insulin resistance (IR), are some of the criteria used to define the MetS. However, criteria for establishing the diagnosis of MetS in childhood have not yet been clearly defined ( 2 , 3 ), although both fatty liver and increased intima thickness have been described already in overweight children ( 4 , 5 ). The need to shed light on the MetS in childhood has led to the identification of some peptides whose serum levels are closely related to the development of IR ( 2 , 6 – 8 ), including neudesin.…”
Section: Introductionmentioning
confidence: 99%
“…DXA is reported to be the best currently available technique for measuring body composition ( 13 , 14 ); however, LBM data may not be accurate because DXA cannot distinguish between body cell mass and water ( 32 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a review of adult data, Berryman and colleagues pointed out that clinical trials with a total number of 982 obese subjects have demonstrated consistent reductions in FM, primarily visceral adipose tissue, without weight-reducing effects, in response to rhGH administration ( 55 ). GH secretion, both in the basal condition and after stimulation tests, is blunted in obesity ( 34 ). Low levels of GH are associated with altered body composition and cardiovascular risk factors ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…High fat intake can cause elevated leptin levels and even leptin resistance [ 73 ]. Leptin stimulates GnRH secretion via the regulation of Kisspeptin neurons [ 74 ], followed by accelerated puberty startup. High fat intake also initiates early puberty by inducing obesity [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%